Metabolic rewiring in cancer-associated fibroblasts provides a niche for oncogenesis and metastatic dissemination. (2nd January 2016) - Liu, Jingyi; Mi, Jun; Zhou, Binhua P.
ABSTRACT: Cancer-associated fibroblasts (CAFs) are major participants in the crosstalk between tumor cells and their microenvironment. CAFs provide not only multiple soluble factors but also metabolic fuels to promote tumor growth, invasion, and metastasis. We discuss recent developments delineating the effects of metabolic symbiosis between CAFs and tumor cells on tumor growth.